Network programmability and automation skills for the next-generation network engineer - Edelman, Jason; Lowe, Scott S.; Oswalt, Matt (O'Reilly Media, 2018)
"This practical guide shows network engineers how to use a range of technologies and tools--including Linux, Python, JSON, and XML--to automate their systems through code. [This book] will help you simplify tasks involved in configuring, managing, and operating network equipment, topologies, services, and connectivity."--Page 4 of cover
Includes index. - Online resource; title from title page (Safari, viewed February 12, 2018)
Keywords: Computer networks -- Management; Scripting languages (Computer science); Réseaux d'ordinateurs; Gestion; Langages de script (Informatique); COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference; Computer networks; Management